“Um transplante de vida” : Medidas de Proteção Social e garantia dos direitos sociais às pessoas com insuficiência renal crônica em espera para transplante renal - Mazera, Lucirley (2016)
Chronic kidney disease, hemodialysis and the possibility of kidney transplantation impose on people who are waiting for transplants, a large wear and a number of limitations involving biological, social, economic and psychological. In this context, the research aimed to analyze the guarantee of social rights to people waiting for kidney transplants from living and the most significant inflections that patients with chronic renal failure attributed to the disease, treatment and kidney transplantation. Through experience we have gathered in this area, with the stage that performed at the University of Barcelona and studies with this research, some aspects deserve our attention: the contribution of public health policies to chronic kidney as a guarantee of social rights, as DRC-154 2004 ANVISA; the related knowledge required to trigger social protection in Brazil highlighting the social security policies from the redesign of the 1988 Constitution; discriminatory process of segregation imposed by the disease; the importance of Social Services action with chronic renal failure on hemodialysis, through their professional action. Therefore, we decided to conduct a quantitative and qualitative research, overcoming prejudice to the numbers and learning to articulate them to the objective and subjective sphere the empirical data can provide. Because of this process were highlighted gaps in the communication process between health teams and users, and in particular the long trajectory of expectation that these patients are exposed. Around these issues have developed a reflection looking forward to the debate the essence of the profession